Sediment dynamics in a dyke breach and across a tidally flooded land surface - Burns, Rachel A.; Mulligan, Ryan P.; Elliott, Megan; van Proosdij, Danika; Murphy, Enda (Frontiers in Marine Science, 2025)
Nature-based solutions may be applied to restore or enhance coastal ecosystem function but should be considered carefully within the context of sediment transport that drives morphological change. This study, for the first time, assesses rates of sediment transport and deposition at a managed dyke realignment site in the critical time period immediately following the dyke breach and before the establishment of salt marsh vegetation. Field observations of water levels and current velocities, suspended sediment concentrations and deposition amounts were collected over 6 tidal cycles at spring tide in areas outside and in the flooded area. A numerical model with a flexible mesh (Delft3D-FM) is applied to simulate the sediment dynamics in a tidal channel, through a dyke breach and into an agricultural site in a macrotidal, mud-dominated estuary using a high-resolution grid to capture the complex topography and bathymetry. The model results enable the intricate spatio-temporal patterns of tidally-driven flows through the breach and over the intertidal flooded area to be revealed, and the important roles in controlling transport and sediment deposition patterns to be identified. The ditches and channels influence flow directions across the intertidal land surface, leading to high current velocities during flood tide, followed by periods of low velocity and particle settling that varies across the marsh surface. The sedimentation rates are estimated to be the same order of magnitude and slightly higher than the relative sea-level rise rate in this area, suggesting this type of marsh will be sustainable. Overall, the numerical results, combined with field observations, provide detailed quantification of the sediment-laden flow through a dyke breach and across the land surface, which is expected to be conducive to salt marsh plant development.